1987
DOI: 10.1002/app.1987.070340219
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of castor oil urethane triamine networks

Abstract: SynopsisCastor oil was polymerized with diisocyanate and crosslinked with primary triamine (Jeffamine T-403) to form networks. The effect of triamine as a crosslinking agent on rubbery castor oil urethane elastomer was determined by measuring network parameters such as average molecular weight between crosslinks (MC) number of polymer chains per unit volume (N), tensile strength, and modulus of the networks. The crosslinking density was varied by varying the ratio of NCO : NH, from 0.60 to 0.95. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…interaction parameter which was calculated using the Equation [11]: The degree of crosslinking (v) and number of chains per unit volume (N) were also calculated using the following relations [12,13]:…”
Section: Results and Disussionmentioning
confidence: 99%
“…interaction parameter which was calculated using the Equation [11]: The degree of crosslinking (v) and number of chains per unit volume (N) were also calculated using the following relations [12,13]:…”
Section: Results and Disussionmentioning
confidence: 99%
“…1,2 The petrochemicalbased monomers used in the manufacturing of polymers, due to their spiraling prices, high rate of depletion of petroleum stocks, as well as carcinogenicity, need to be replaced by polymers derived from sustainable and eco-friendly resources like vegetable seed oils. [3][4][5][6] N,N-bis-(2 hydroxyethyl) oil fatty amides have been used as monomer in the preparation of many oilbased polyesteramide (PEA) resins by reaction with dibasic acids or anhydrides.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids from linseed and other vegetable oils have long been used as a sustainable resource in the production of industrially important decorative and anticorrosive coating materials 1, 2. The petrochemical‐based monomers used in the manufacturing of polymers, due to their spiraling prices, high rate of depletion of petroleum stocks, as well as carcinogenicity, need to be replaced by polymers derived from sustainable and eco‐friendly resources like vegetable seed oils 3–6…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Generally, polyesteramide coatings are obtained by baking at and above 175°C. 4,5 To improve the physicomechanical and anticorrosive characteristics of baked coatings, we incorporated aluminum in the backbone of the polymer. 6 We found that the aforementioned properties of the coatings were enhanced appreciably in the case of alumina-filled polyesteramides.…”
Section: Introductionmentioning
confidence: 99%